2007
DOI: 10.1007/s10935-007-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Workplace Laughter Groups on Personal Efficacy Beliefs

Abstract: This study measured the impact of a purposeful aerobic laughter intervention on employees' sense of self-efficacy in the workplace. Participants were 33 employees of a behavioral health center. They met for 15-minute sessions on 15 consecutive workdays and engaged in a guided program of non-humor dependent laughter. The primary outcome measure was the Capabilities Awareness Profile, a self-report self-efficacy questionnaire. Employees demonstrated a significant increase in several different aspects of self-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 16 publications
1
23
0
4
Order By: Relevance
“…Mood also increased, though not to the same extent. The finding that positive emotions increase following an induced laughter intervention is consistent with previous research (Dolgoff-Kaspar et al 2012;Suraj-Narayan & Surajnarayan 2011;Beckman, Regier & Young 2007). Specifically, the increased GLS is consistent with the findings of Shahidi et al (2011) who found that elderly participants diagnosed with depression also reported increases in GLS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mood also increased, though not to the same extent. The finding that positive emotions increase following an induced laughter intervention is consistent with previous research (Dolgoff-Kaspar et al 2012;Suraj-Narayan & Surajnarayan 2011;Beckman, Regier & Young 2007). Specifically, the increased GLS is consistent with the findings of Shahidi et al (2011) who found that elderly participants diagnosed with depression also reported increases in GLS.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have been reported in an organisational context. Employees who completed 15 sessions of laughter yoga reported significant improvements in perceived self-efficacy in the workplace, and experienced sustained positive emotions at a 90-day follow-up (Beckman, Regier & Young 2007).…”
Section: Introductionmentioning
confidence: 95%
“…For example, Beckman, Regier, and Young (2007) measured the impact of a purposeful aerobic laughter intervention on employees' happiness. Participants met for 15-min sessions on 15 consecutive workdays and engaged in a guided program of non-humor-dependent laughter.…”
mentioning
confidence: 99%
“…Nicméně smích a humor je třeba odlišovat. Beckman, Regier, a Young (2007) hovoří o kognitivních účincích v případě humoru, v případě smíchu o účincích fyzických. Různost je patrná i v původech pojmů.…”
Section: Výsledkyunclassified